The need to improve health care in prisons - Fernandes, Luiz Henrique (Faculdade de Saúde Pública da Universidade de São Paulo, 2014)
OBJECTIVE: To analyze physical structure, working conditions of health professionals and outline of the procedures established in prisons. METHODS: We analyzed 34 provisional detention centers and 69 male and six female prison units in the state of Sao Paulo, Southeastern Brazil, in 2009. A self-applied instrument was developed to collect quantitative data on the characteristics of health care structure, equipment and personnel in prisons. Analysis of variance (ANOVA) or equivalent non-parametric tests and Chi-square or Fisher’s tests were used to compare categorical and continuous variables, respectively, between the groups. RESULTS: The main problems were delays in the results of laboratory tests and imaging. With respect to the teams, it was observed that a large majority were in conditions close to those proposed by the Bipartite Commission 2013 but without improvement being reflected in the indicators. With respect to the process, more than 60.0% of prisons located in small towns do not have the structural conditions to ensure secondary or tertiary health care for the continuity of treatment. CONCLUSIONS: This profile of prisons in the country can be used for planning and monitoring future actions for the continuous improvement of healthcare processes.